Phosphorus-carbon composite material, manufacturing method of phosphorus-carbon composite material, negative electrode active material, negative electrode for lithium secondary battery and lithium secondary battery
A thermally stable phosphorus-carbon composite material with a core-shell structure addresses the durability and capacity issues of conventional negative electrode materials, enhancing the performance of lithium secondary batteries.
Patent Information
- Application Number
- JP2024164964
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-13
AI Technical Summary
Conventional negative electrode active materials for lithium secondary batteries require improvement in durability and charge/discharge capacity to achieve highly reliable and high-performance batteries.
A phosphorus-carbon composite material with specific mass content ratios of phosphorus and carbon, thermally stable, and containing a bond between phosphorus and carbon atoms, produced through a mixing and pulverization process involving compression, which forms a core-shell structure.
The phosphorus-carbon composite material enhances the initial charge/discharge capacity and cycle characteristics of lithium secondary batteries, providing a novel and stable negative electrode active material.
Smart Images

Figure 2024173980000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a phosphorus-carbon composite material, a method for producing the phosphorus-carbon composite material, a negative electrode active material, a negative electrode for a lithium secondary battery, and a lithium secondary battery. [Background technology]
[0002] Lithium secondary batteries are used as power sources for small electronic devices such as mobile phones, notebook computers, etc. In recent years, lithium secondary batteries have also been put to practical use as medium- or large-sized power sources for automobiles and power storage applications.
[0003] Carbon materials are known as negative electrode active materials for lithium secondary batteries. Conventionally, negative electrode active materials in which phosphorus is further contained in a carbon material for the purpose of improving battery performance have been known (see, for example, Patent Document 1). In the negative electrode active material described in Patent Document 1, the negative electrode active material containing a carbon material further contains phosphorus, thereby making it possible to provide a negative electrode with excellent charge / discharge capacity. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 11-67207 Summary of the Invention [Problem to be solved by the invention]
[0005] In order to obtain a highly reliable and high-performance lithium secondary battery, a negative electrode active material that is excellent not only in charge and discharge capacity but also in durability is required. Conventional negative electrode active materials still have room for improvement in order to improve the performance of lithium secondary batteries.
[0006] The present invention has been made in view of the above circumstances, and has an object to provide a novel phosphorus-carbon composite material containing phosphorus and carbon. Another object is to provide a method for producing such a novel phosphorus-carbon composite material that enables suitable production of such a novel phosphorus-carbon composite material. Another object is to provide a negative electrode active material, a negative electrode for a lithium secondary battery, and a lithium secondary battery that contain such a novel phosphorus-carbon composite material. [Means for solving the problem]
[0007] In order to solve the above problems, one aspect of the present invention includes the following aspects.
[0008] [1] A phosphorus-carbon composite material containing phosphorus atoms and carbon atoms, the phosphorus atom content in the phosphorus-carbon composite material being 10% by mass or more and 95% by mass or less, the carbon atom content in the phosphorus-carbon composite material being 5% by mass or more and 90% by mass or less, and a weight loss rate WL at a measurement temperature of 620°C obtained by thermogravimetry under the following conditions: 620 and the weight loss rate WL at the measurement temperature of 780°C 780 Compared to WL 620 / WL 780 is 0.1 or more and 0.9 or less. (Thermogravimetric measurement) A 10 mg sample of the phosphorus-carbon composite material is precisely weighed and used as a sample. Using a thermogravimetric analyzer, the sample is heated from 50°C to 780°C at a heating rate of 10°C / min under a nitrogen stream, and the change in weight is measured. (Weight reduction rate) The ratio of the weight of the sample at the measurement temperature to the weight of the precisely weighed sample is defined as the weight loss rate (wt %) at the measurement temperature.
[0009] [2] Weight loss rate WL at a measurement temperature of 300°C obtained by the above thermogravimetry 300 and the weight loss rate WL at a measurement temperature of 600°C 600 Compared to WL 300 / WL 600 The phosphorus-carbon composite material according to [1], wherein
[0010] [3] The phosphorus-carbon composite material according to [1] or [2], which has a peak in an XPS spectrum indicating a bond between a phosphorus atom and a carbon atom.
[0011] [4] In the XRD profile measured using CuKα radiation, the intensity I at 2θ=20° 20 , Intensity I at 2θ=26.3° 26.3 , and the intensity at 2θ=40° I 40 The phosphorus-carbon composite material according to any one of [1] to [3], which satisfies the following formulas (1) to (3): |P| / |B|<2 …(1) P=I 26.3 -I 40 …(2) B=(I 20 -I 40 ) × (26.3-40) / (20-40) … (3)
[0012] [5] The phosphorus-carbon composite material according to any one of [1] to [4], comprising a core particle containing phosphorus atoms and a carbon coating covering a surface of the core particle.
[0013] [6] A method for producing a phosphorus-carbon composite material, comprising the step of compounding a carbon material and phosphorus by a co-pulverizing process involving compression.
[0014] [7] A method for producing a phosphorus-carbon composite material, comprising the step of ball milling a carbon material and phosphorus.
[0015] [8] The method for producing a phosphorus-carbon composite material according to [6] or [7], wherein the carbon material is at least one selected from the group consisting of amorphous carbon, graphite, porous carbon, mesocarbon microbeads, fullerene, carbon nanotubes, graphene, graphene oxide, carbon nitrite (C3N4), and laminated carbon nanofibers.
[0016] [9] The method for producing a phosphorus-carbon composite material according to any one of [6] to [8], wherein the phosphorus is black phosphorus.
[0017]
[10] A negative electrode active material comprising the phosphorus-carbon composite material according to any one of [1] to [5].
[0018]
[11] A negative electrode for a lithium secondary battery, comprising the negative electrode active material according to
[10] .
[0019]
[12] A lithium secondary battery comprising the negative electrode for lithium secondary batteries according to
[11] . Effect of the Invention
[0020] According to the present invention, it is possible to provide a novel phosphorus-carbon composite material containing phosphorus and carbon. It is also possible to provide a method for producing such a novel phosphorus-carbon composite material that enables suitable production of such a novel phosphorus-carbon composite material. Furthermore, it is also possible to provide a negative electrode active material, a negative electrode for a lithium secondary battery, and a lithium secondary battery that contain such a novel phosphorus-carbon composite material. [Brief description of the drawings]
[0021] [Figure 1] FIG. 1 is a graph showing the results of thermogravimetric measurements on PC materials and PC blends. [Diagram 2] FIG. 2 shows the XPS spectra of the PC material and the PC blend. [Diagram 3] FIG. 3 is a transmission electron microscope (TEM) photograph of the PC material. [Figure 4] FIG. 4 shows the XRD profiles of the PC material and the PC blend. [Diagram 5] FIG. 5 is a schematic diagram showing an example of a lithium secondary battery. [Figure 6] FIG. 6 is a schematic diagram showing an example of an all-solid-state lithium secondary battery. [Figure 7] FIG. 7 is a graph showing the results of thermogravimetry of the PC materials prepared in Examples 1 and 4 to 7, and the PC mixture prepared in Comparative Example 2. [Figure 8] FIG. 8 shows XPS spectra of the PC materials prepared in Examples 1 to 5 and 7. [Figure 9] FIG. 9 shows XRD profiles of the PC materials produced in Examples 1 to 7 and the PC mixtures produced in Comparative Examples 1 and 2. [Figure 10] FIG. 10 is a graph showing the discharge capacities up to 100 cycles of the lithium secondary batteries using the PC materials of Examples 1 to 7 and Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] Hereinafter, a method for producing a phosphorus-carbon composite material, a negative electrode active material, a negative electrode for a lithium secondary battery, and a lithium secondary battery according to the present embodiment will be described with reference to Fig. 1 to Fig. 6. In all the following drawings, the dimensions and ratios of each component are appropriately changed to make the drawings easier to see.
[0023] Phosphorus-carbon composite material The phosphorus-carbon composite material of the present embodiment contains phosphorus atoms and carbon atoms. In the following description, the "phosphorus-carbon composite material" may be abbreviated to simply "PC material."
[0024] The PC material has a phosphorus atom content of 10% by mass or more and 95% by mass or less. In addition, the carbon atom content of the PC material is 5% by mass or more and 90% by mass or less. When the PC material is composed of phosphorus atoms and carbon atoms, the sum of the carbon atom content and the phosphorus atom content in the PC material is 100% by mass. Even when the PC material is composed of carbon atoms and phosphorus atoms, impurities that are inevitably mixed in from the raw materials and manufacturing process of the PC material are permitted.
[0025] The PC material is composed of 60 mass % or more of phosphorus atoms and carbon atoms, and may further contain elements other than phosphorus atoms and carbon atoms. Elements other than phosphorus and carbon atoms contained in PC materials include lithium, silicon, germanium, tin, aluminum, zinc, magnesium, transition metals, nitrogen, oxygen, fluorine, silicon, titanium, niobium, sulfur, and chlorine. These can be used as raw materials from metal oxides, composite metal oxides, metal fluorides, metal sulfides, metal chlorides, silicon oxides, silicates, titanates, and aluminates.
[0026] The content of phosphorus atoms, the content of carbon atoms, and the contents of other atoms that may be contained in the PC material can be determined by known ICP analysis.
[0027] In the PC material, the content of the phosphorus atoms is preferably 20% by mass or more, more preferably 30% by mass or more, and even more preferably 50% by mass or more. The higher the phosphorus content, the higher the initial charge / discharge capacity of the PC material. In addition, in the PC material, the content of the phosphorus atoms is preferably 90% by mass or less, more preferably 80% by mass or less, and even more preferably 75% by mass or less. This is because if the content of phosphorus atoms is too high, the cycle characteristics of the PC material are reduced. The upper and lower limits of the content of phosphorus atoms can be arbitrarily combined.
[0028] In the PC material, the carbon atom content is preferably 10% by mass or more, more preferably 20% by mass or more, and even more preferably 25% by mass or more. The higher the carbon atom content, the higher the cycle characteristics of the PC material. In the PC material, the carbon atom content is preferably 80% by mass or less, more preferably 70% by mass or less, and even more preferably 50% by mass or less. If the carbon atom content is too high, the initial charge / discharge capacity of the PC material decreases. The upper and lower limits of the carbon atom content can be combined in any way.
[0029] As will be described in detail later, the PC material can be produced by mixing phosphorus and a carbon material in a ball mill. The inventors conducted a detailed analysis and investigation of the obtained PC material and confirmed that the PC material is not a simple mixture of the raw materials phosphorus and carbon material, but is a new material in which phosphorus atoms and carbon atoms are chemically bonded (covalently bonded) and have physical properties different from those of the raw materials phosphorus and carbon materials.
[0030] The physical properties of the PC material will be described in detail below, in comparison with a mixture of phosphorus and a carbon material (hereinafter sometimes referred to as a "PC mixture").
[0031] In the following explanation, an example of a PC material is compared with an example of a mixture in which the same raw materials as the PC material are mixed in a mortar. In the example shown below, the raw materials of the PC material and the PC mixture both contain black phosphorus and a carbon material in a mass ratio of 6:4. In both the PC material and the PC mixture, CSCNT (cup-stacked carbon nanotube) is used as the carbon material.
[0032] [Heat behavior] The weight loss rate (WL) of PC material at a measurement temperature of 620°C is obtained by thermogravimetry under the following conditions. 620 and the weight loss rate WL at the measurement temperature of 780°C 780 Compared to WL 620 / WL 780 is greater than or equal to 0.1 and less than or equal to 0.9. (Thermogravimetric measurement) A 10 mg sample of the phosphorus-carbon composite material is precisely weighed and used as a sample. Using a thermogravimetric analyzer, the sample is heated from 50°C to 780°C at a heating rate of 10°C / min under a nitrogen stream, and the change in weight is measured. (Weight reduction rate) The ratio of the weight of the sample at the measurement temperature to the weight of the precisely weighed sample is defined as the weight loss rate (wt %) at the measurement temperature.
[0033] Figure 1 is a graph showing the results of the thermogravimetric measurements of the PC material and the PC mixture. In Figure 1, the horizontal axis shows the heating temperature (°C) and the vertical axis shows the weight loss rate (wt%) relative to the sample weight. In Figure 1, the symbol A shows the behavior of the PC material, and the symbol X shows the behavior of the PC mixture.
[0034] As shown in Figure 1, for the PC mixture, the weight loss rate WL at the measurement temperature of 620°C was 620 (Indicated by symbol X1 in FIG. 1) and the weight loss rate WL at a measurement temperature of 780°C 780 (In Fig. 1, the ratio WL 620 / WL 780 The PC mixture shows a steep weight loss at measurement temperatures of 350°C to 450°C, and at 620°C, the sample loses about 60% of its initial weight.
[0035] This weight loss is considered to correspond to the weight of the raw material black phosphorus. In the case of the PC mixture, the black phosphorus contained in the PC mixture is considered to have been lost due to heating. It is known that black phosphorus changes into its allotrope red phosphorus when heated to 125°C. Red phosphorus is also known to sublime at 416°C under normal pressure.
[0036] In contrast, the weight loss rate of the PC material at a measurement temperature of 620°C was WL 620 (Indicated by symbol A1 in FIG. 1) and the weight loss rate WL at a measurement temperature of 780°C 780 (In Fig. 1, the ratio WL 620 / WL 780 is between 0.1 and 0.9.
[0037] In addition, the PC material has a weight loss rate (WL) of 300°C measured by the thermogravimetry mentioned above. 300 (Indicated by symbol A3 in FIG. 1) and the weight loss rate WL at a measurement temperature of 600°C 600 (In Fig. 1, the ratio WL 300 / WL 600 It is preferable that the ratio is in the range of -0.1 to 0.1.
[0038] That is, unlike the PC mixture, the PC material hardly loses weight up to a measurement temperature of 300°C and is thermally stable at the measurement temperature of 300°C.
[0039] W.L. 620 / WL 780 is preferably 0.1 or more, more preferably 0.3 or more, and even more preferably 0.5 or more. 620 / WL 780 is preferably 0.9 or less, more preferably 0.8 or less. 620 / WL 780 The upper and lower limits can be combined in any desired manner.
[0040] W.L. 300 / WL 600 is preferably -0.1 or more, and more preferably -0.08 or more. 300 / WL 600 is preferably 0.1 or less, more preferably 0.08 or less. 300 / WL 600 The upper and lower limits can be combined in any desired manner.
[0041] From the results shown in Figure 1, it is believed that the black phosphorus used as a raw material in the PC material changes, becoming a substance that behaves differently from black phosphorus when exposed to heat.
[0042] [PC bonding] The PC material has a peak indicative of a bond between a phosphorus atom and a carbon atom in the XPS spectrum. It is known that the "peak indicative of a bond between a phosphorus atom and a carbon atom" appears in the range of 132 to 136 eV in the XPS spectrum. In the following description, the bond between a phosphorus atom and a carbon atom may be simply referred to as a "PC bond."
[0043] Figure 2 shows the XPS spectra of the PC material and the PC mixture. In Figure 2, the horizontal axis shows binding energy (eV) and the vertical axis shows the number of detected photoelectrons (cps (counts per second)). In Figure 2, the symbol A indicates the PC material and the symbol X indicates the PC mixture.
[0044] (XPS spectrum measurement conditions) The XPS spectrum is measured under the following measurement conditions. Measurement equipment: XPS device, ESCA-3400 (Shimadzu Corporation) ·Radiation source: Mg Kα radiation (20mA, 10kV) When a peak is detected in the range of 132 to 136 eV, it is determined that a PC bond is present.
[0045] As shown in FIG. 2, no peak indicating a PC bond was detected in the range of 132 to 136 eV in the PC mixture, but a peak indicating a PC bond (indicated by the symbol α) was detected in the PC material.
[0046] From the results shown in Figure 2, it is believed that the PC material is a substance having a chemical bond between the phosphorus atom and the carbon atom.
[0047] [exterior] The PC material has a core particle containing phosphorus atoms and a carbon coating covering the surface of the core particle.
[0048] Fig. 3 is a transmission electron microscope (TEM) photograph of the PC material. As shown in Fig. 3, a particle 50 of the PC material has a core-shell structure in which a carbon film 52 covers the surface of a core particle 51 containing phosphorus atoms.
[0049] The presence of phosphorus and carbon atoms in the PC material can be confirmed by using EDX (Energy Dispersive X-ray Spectroscopy).
[0050] Furthermore, when the PC material is composed only of phosphorus atoms and carbon atoms, the heavier phosphorus atoms appear darker in the TEM photograph, so it can be easily determined from the TEM photograph that the core particle 51 contains phosphorus atoms and has a core-shell structure covered with a carbon film 52 containing carbon atoms.
[0051] (TEM photographing conditions) TEM photographs are taken under the following imaging conditions. TEM equipment: Transmission electron microscope H-9000NAR (Hitachi, Ltd.) Field of view: Maximum 500nm x 500nm. At least some of the particles of the PC material must be included in the field of view.
[0052] In addition to satisfying the above-mentioned requirements regarding [thermal behavior], the PC material preferably has the above-mentioned core-shell structure.
[0053] [Crystalline state] Figure 4 shows XRD profiles of the PC material and the PC mixture. In Figure 4, the horizontal axis shows the diffraction angle (2θ, °) and the vertical axis shows the diffracted X-ray intensity (au). In Figure 4, the symbol A indicates the PC material and the symbol X indicates the PC mixture.
[0054] (XRD profile measurement conditions) The XRD profile is measured under the following measurement conditions. Measurement equipment: Horizontal sample multipurpose X-ray diffraction instrument Ultima IV (Rigaku Corporation) ·Radiation source: Cu Kα radiation Measurement range (2θ): 10°~90° Scan speed: 4° / min Sampling: 0.02° Voltage 40kV, current 40mA
[0055] As shown in Figure 4, in the PC mixture, the carbon material and black phosphorus each have a certain degree of crystallinity and show diffraction peaks. In contrast, in the PC material, the diffraction peaks seen in the PC mixture were not observed, and only noise was confirmed over the entire measurement range. In other words, from the results shown in Figure 4, it is believed that in the PC material, the crystallinity of the carbon material used as the raw material has been lost and it has become amorphous, or the carbon material has become so fine that the crystalline state cannot be confirmed.
[0056] Here, when the XRD profile of the PC material is measured under the above conditions, the intensity I at 2θ=20° in the XRD profile measured under the above conditions is 20 , Intensity I at 2θ=26.3° 26.3 , and the intensity at 2θ=40° I 40 satisfies the following relations (1) to (3). |P| / |B|<2 …(1) P=I 26.3 -I 40 …(2) B=(I 20 -I 40 ) × (26.3-40) / (20-40) … (3)
[0057] When the XRD profile of the raw carbon material is measured, the peak of the carbon material appears at 2θ=26.3°, which corresponds to the graphite (002) peak. On the other hand, in the XRD profile of a normal carbon material, there are no peaks at 2θ=20° or 2θ=40°. Therefore, in the above formula (1), 2θ=40°, where there is no carbon material peak, is set as the reference point, and the state of the carbon material can be determined by comparing the intensity of the reference point in the XRD profile with the intensity at the position (2θ=26.3°) where the peak of the raw carbon material exists.
[0058] "P" expressed in the above formula (2) is the intensity of the reference point I 40 and the intensity I at the position where the carbon material peak exists 26.3 and indicates the difference of the peak from the reference point.
[0059] "B" in the above formula (3) indicates the baseline intensity at 2θ=26.3°, estimated from two positions (2θ=20° and 2θ=40°) where there are no peaks.
[0060] The ratio of the baseline intensity from the reference point to the peak intensity can be calculated from the ratio of the absolute values of P and B (|P| / |B|) expressed by the above formula (1). When |P| / |B| is 2 or more, it indicates the presence of a peak of a carbon material.
[0061] On the other hand, when |P| / |B| is less than 2 and satisfies formula (1), the peak of the carbon material is reduced, and the crystallinity of the carbon material is reduced, so that the carbon material is amorphous, or the carbon material is so fine that the crystalline state cannot be confirmed. Therefore, it is preferable that the PC material satisfies the above-mentioned requirements for [thermal behavior], as well as the above-mentioned relational expressions (1) to (3).
[0062] As described above, the PC material is a novel substance that differs from the mixture of the raw material phosphorus (black phosphorus in Figures 1 to 4) and a carbon material in terms of its thermal behavior, bonding state, appearance, and crystalline state.
[0063] <Production method of phosphorus-carbon composite material> As described above, the PC material can be produced by a production method including a step of compounding a carbon material and phosphorus by a co-grinding process involving compression.
[0064] In the above-mentioned production method, the carbon material, which is the raw material, can be at least one selected from the group consisting of amorphous carbon, graphite, porous carbon, mesocarbon microbeads (MCMB), fullerene, carbon nanotubes, graphene, graphene oxide, carbon nitrite (C3N4), and laminated carbon nanofibers (Carbon nanfibers platelets). All of these carbon materials have a graphite structure.
[0065] Examples of amorphous carbon include carbon black (CB), acetylene black (AB), ketjen black, hard carbon, and soft carbon.
[0066] As for fullerenes, C 60 , C 72 , C 84 etc. can be mentioned.
[0067] Examples of carbon nanotubes include single-walled carbon nanotubes (SWCNTs), multi-walled carbon nanotubes (MWCNTs), cup-stacked carbon nanotubes (CSCNTs), and vapor grown carbon fiber (VGCF) carbon nanofibers. These have a structure that extends in one axial direction (one-dimensional structure).
[0068] Graphene, graphene oxide, carbon nitrite (C3N4), and laminated carbon nanofibers (carbon nanofibers platelets) have a structure that extends in the plane direction (two-dimensional structure).
[0069] In carbon materials, the ends (edge sites) of the graphite structure are more active than non-edge sites. Therefore, it is assumed that most of the PC bonds are formed at the edge sites of the carbon material. Therefore, from the viewpoint of facilitating the formation of PC bonds, it is preferable to use a carbon material that has many edge sites.
[0070] Examples of carbon materials with many edge sites include CSCNT, graphite, mesocarbon microbeads (MCMB), graphene, graphene oxide, carbon nitrite (C3N4), and laminated carbon nanofibers. Among these, CSCNT is preferred as the carbon material.
[0071] In the above-mentioned production method, any of the known phosphorus allotropes can be used as the raw material phosphorus. Of the phosphorus allotropes, black phosphorus is preferred because it is the most chemically stable and a good conductor of electricity.
[0072] In the above manufacturing method, the "mixed and crushed process with compression" refers to a process in which a compressive force is applied to multiple types of powdered raw materials to mix and crush the raw materials. It is believed that by subjecting the carbon material and phosphorus to the mixed and crushed process with compression, a strong impact force is applied to the carbon material and phosphorus, and at the same time, a chemical change occurs that cannot be obtained with a normal mixture. As a result, it is believed that a PC bond that is not present in the raw materials is formed as a product, and a PC material that does not exhibit the crystalline state seen in the raw materials is obtained.
[0073] The "mixed grinding process with compression" should be carried out until the peaks derived from the raw materials disappear in the XRD profile of the mixed material, or until the occurrence of PC bonds can be confirmed in the XPS spectrum of the mixed material.
[0074] Examples of processing devices (crushers) capable of mixing and crushing with compression include roller mills, jet mills, hammer mills, pin mills, disk mills, rod mills, ball mills, vibration mills, attritors, and bead mills. In the production of PC materials, it is preferable to use an agitation type crusher equipped with a crushing vessel and a rotor, particularly because mixing and crushing can be performed simultaneously. Examples of agitation type crushers include pin mills, disk mills, rod mills, ball mills, vibration mills, attritors, and bead mills.
[0075] Furthermore, as the processing device, a media-agitation type mill is preferred because it can mix and pulverize the raw material powder while simultaneously applying a strong impact force to the carbon material and phosphorus. Examples of media-agitation type mills include ball mills, vibration mills, attritors, and bead mills. Among these, a ball mill is particularly preferred as a mill from the viewpoint of easily controlling the property conditions.
[0076] It is believed that the ball mill mixing first causes the atomization of phosphorus and the decomposition of the carbon material, followed by the formation of PC bonds. During this ball mill mixing process, phosphorus becomes the above-mentioned core particles.
[0077] It is believed that the above-mentioned carbon film is then formed around the core particle containing phosphorus atoms, resulting in a composite material, which in turn results in the PC material.
[0078] During ball mill mixing, the manufacturing conditions can be controlled by adjusting the rotation speed of the ball mill, the amount of media (balls) to the raw materials (ball powder ratio), and the mixing time. In other words, adjusting conditions such as increasing the rotation speed of the ball mill, increasing the amount of media to the raw materials, and lengthening the mixing time promotes the mixing of phosphorus and carbon materials, making it easier to obtain PC materials. Controlling the above manufacturing conditions promotes the formation of PC bonds and reduces WL 620 / WL 780 It is easy to produce PC materials that satisfy the following:
[0079] The balls are grinding media for grinding metal materials. The diameter of the balls is the average particle size of the balls. The balls flow at high speed inside the grinding container of the grinding machine by the rotation of the grinding container itself, and collide with the powder raw material containing the carbon material and phosphorus, grinding it into particles with a smaller average particle size. In the grinding process, it is preferable that the grinding container and beads are not excessively worn. Therefore, the shape of the balls is preferably spherical or ellipsoidal.
[0080] The diameter of the balls is preferably larger than the average particle size of the PC material after grinding. By using such balls, a large amount of grinding energy can be applied to the metal material, making it possible to obtain metal particles efficiently in a short time. On the other hand, if the diameter of the balls is too large, it promotes re-agglomeration of the PC material, resulting in PC material with a wide particle size distribution.
[0081] The diameter of the balls is preferably 0.1 to 10 mm, more preferably 1 to 10 mm. When the diameter of the balls is within this range, the formation of PC bonds is promoted and re-agglomeration can be suppressed. The diameter of the balls to be put into the grinding container may be uniform or may vary.
[0082] The balls may be made of glass, agate, alumina, zirconia, stainless steel, chrome steel, tungsten carbide, silicon carbide, or silicon nitride. Among these, zirconia is preferred because it has a relatively high hardness and is therefore less prone to wear, and because it has a relatively high specific gravity and therefore is capable of producing a large amount of grinding energy. By using these balls, the raw powder of the PC material can be efficiently ground.
[0083] The weight ratio of the balls to the raw powder of the PC material is called the ball powder ratio. By increasing the ball powder ratio, a strong impact force can be applied to the raw powder of the PC material at a high frequency, and the formation of PC bonds can be further promoted. If the ball powder ratio is too high, the production amount of the PC material per unit operation decreases. Therefore, the ball powder ratio is preferably 0.5 to 500, more preferably 1 to 200, and even more preferably 10 to 200.
[0084] After the ball mill mixing is completed, the balls are separated from the PC material using a filter, etc. and separate.
[0085] The fact that the above-mentioned PC material has been obtained by ball mill mixing can be confirmed by measuring the XRD profile of the mixed material and seeing the disappearance of the peaks derived from the raw materials as shown in Figure 4. The duration of ball mill mixing should be determined by conducting a preliminary experiment to determine the relationship between the mixing time and the time until the peaks derived from the raw materials disappear. In other words, ball mill mixing should be performed until the peaks derived from the raw materials disappear in the XRD profile of the mixed material.
[0086] Alternatively, the XPS spectrum of the mixed material may be measured to confirm the occurrence of PC bonds as shown in Figure 2. In this case, the duration of ball mill mixing may be determined by conducting a preliminary experiment to determine the relationship between the mixing time and the time required for PC bonds to occur. In other words, ball mill mixing may be continued until the occurrence of PC bonds can be confirmed in the XPS spectrum of the mixed material.
[0087] In ball mill mixing, strong impacts (pressures) are applied locally to the carbon materials and phosphorus due to collisions between media and between the media and the ball mill container. Although the details are unclear, it is believed that the application of such impacts causes chemical changes that cannot be obtained with normal mixtures, forming PC bonds that are not present in the raw materials, resulting in PC materials that do not exhibit the crystalline state seen in the raw materials.
[0088] Therefore, according to the manufacturing method of this embodiment, the carbon material and phosphorus are mixed and crushed with compression, so that the above-mentioned PC material can be easily manufactured.
[0089] Moreover, according to the manufacturing method of this embodiment, the above-mentioned PC material can be easily manufactured by the simple method of mixing the carbon material and phosphorus in a ball mill.
[0090] 《Negative electrode active material》 The negative electrode active material of this embodiment includes the above-mentioned PC material.
[0091] The negative electrode active material may be the above-mentioned PC material alone, or may contain other known materials used as negative electrode active materials in addition to the PC material. Such materials include (i) carbon materials capable of inserting and extracting lithium ions, (ii) alloy-based negative electrode active material materials that form a lithium alloy phase, (iii) transition metal oxides that undergo a decomposition and regeneration reaction (conversion reaction) with lithium ions, and (iv) oxides or composite oxides that have activity as negative electrode active materials.
[0092] (i) Carbon materials include graphite, hard carbon, soft carbon, and carbon nanotubes.
[0093] (ii) Examples of alloy-based negative electrode active materials include metals such as silicon, germanium, tin, aluminum, zinc, and magnesium, and alloys thereof.
[0094] (iii) Examples of transition metal oxides include manganese oxide, iron oxide, cobalt oxide, nickel oxide, copper oxide, and magnesium oxide. These oxides may be composite metal oxides further containing other metals (e.g., lithium).
[0095] (iv) Examples of oxides or composite oxides include titanium oxide, lithium titanate, and silicon oxide.
[0096] <Negative electrode for lithium secondary batteries> The negative electrode for a lithium secondary battery according to the present embodiment includes the above-mentioned negative electrode active material. In addition to the negative electrode active material, the negative electrode for a lithium secondary battery also has a current collector and a binder for binding the negative electrode active material to the current collector. The current collector and the binder may have a known structure.
[0097] The current collector is preferably made of copper or a copper alloy.
[0098] As the binder, polyvinylidene fluoride (hereinafter sometimes referred to as PVdF) can be suitably used.
[0099] <Lithium secondary battery> The lithium secondary battery of this embodiment includes the above-mentioned negative electrode for lithium secondary batteries (hereinafter, negative electrode).
[0100] An example of a suitable lithium secondary battery when using the negative electrode active material of this embodiment has a positive electrode and a negative electrode, a separator sandwiched between the positive electrode and the negative electrode, and an electrolyte solution disposed between the positive electrode and the negative electrode.
[0101] An example of a lithium secondary battery has a positive electrode and a negative electrode, a separator sandwiched between the positive electrode and the negative electrode, and an electrolyte disposed between the positive electrode and the negative electrode.
[0102] 5 is a schematic diagram showing an example of a lithium secondary battery. The cylindrical lithium secondary battery 10 of this embodiment is manufactured as follows.
[0103] First, as shown in FIG. 5 , a pair of strip-shaped separators 1, a strip-shaped positive electrode 2 having a positive electrode lead 21 at one end, and a strip-shaped negative electrode 3 having a negative electrode lead 31 at one end are laminated in the order of separator 1, positive electrode 2, separator 1, and negative electrode 3, and then wound to form an electrode group 4.
[0104] Next, the electrode group 4 and an insulator (not shown) are housed in the battery can 5, the bottom of the can is sealed, the electrode group 4 is impregnated with an electrolyte solution 6, and the electrolyte is disposed between the positive electrode 2 and the negative electrode 3. Furthermore, the upper part of the battery can 5 is sealed with a top insulator 7 and a sealing body 8, whereby a lithium secondary battery 10 can be manufactured.
[0105] The shape of the electrode group 4 can be, for example, a columnar shape such that the cross-sectional shape when the electrode group 4 is cut perpendicular to the winding axis is a circle, an ellipse, a rectangle, or a rectangle with rounded corners.
[0106] The shape of a lithium secondary battery having such an electrode group 4 can be any shape defined by IEC60086, which is a standard for batteries defined by the International Electrotechnical Commission (IEC), or JIS C 8500. For example, cylindrical or rectangular shapes can be used.
[0107] Furthermore, the lithium secondary battery is not limited to the above-mentioned wound type configuration, and may be a laminated type configuration in which a laminated structure of a positive electrode, a separator, a negative electrode, and a separator is repeatedly stacked. Examples of the laminated type lithium secondary battery include a so-called coin type battery, a button type battery, and a paper type (or sheet type) battery.
[0108] Each component will be described in order below. (positive electrode) The positive electrode can be produced by preparing a positive electrode mixture containing a positive electrode active material, a conductive material, and a binder, and supporting the positive electrode mixture on a positive electrode current collector.
[0109] (Cathode active material) The positive electrode active material may be a lithium-containing compound or other metal compound. Examples of the lithium-containing compound include a lithium cobalt composite oxide having a layered structure, a lithium nickel composite oxide having a layered structure, a lithium manganese composite oxide having a spinel structure, and a lithium iron phosphate having an olivine structure.
[0110] Other metal compounds include, for example, oxides such as titanium oxide, vanadium oxide, and manganese dioxide, and sulfides such as titanium sulfide and molybdenum sulfide.
[0111] (Conductive material) The conductive material of the positive electrode may be a carbon material, such as graphite powder, carbon black (e.g., acetylene black), or a fibrous carbon material.
[0112] The proportion of the conductive material in the positive electrode mixture is preferably 5 to 20 parts by mass per 100 parts by mass of the positive electrode active material.
[0113] (binder) The binder of the positive electrode may be a thermoplastic resin. Examples of the thermoplastic resin include polyimide resins, fluororesins such as polyvinylidene fluoride (PVdF) and polytetrafluoroethylene, polyolefin resins such as polyethylene and polypropylene, and resins described in WO2019 / 098384A1 or US2020 / 0274158A1.
[0114] (Positive electrode current collector) The positive electrode current collector of the positive electrode can be a strip-shaped member made of a metal material such as Al, Ni or stainless steel.
[0115] As a method for supporting the positive electrode mixture on the positive electrode current collector, there can be mentioned a method in which the positive electrode mixture is made into a paste using an organic solvent, the obtained paste of the positive electrode mixture is applied to at least one side of the positive electrode current collector, dried, and fixed by performing an electrode pressing process.
[0116] When the positive electrode mixture is made into a paste, an example of an organic solvent that can be used is N-methyl-2-pyrrolidone (hereinafter sometimes referred to as NMP).
[0117] Examples of methods for applying the positive electrode mixture paste to the positive electrode current collector include slit die coating, screen coating, curtain coating, knife coating, gravure coating, and electrostatic spraying. The positive electrode can be produced by the above-mentioned methods.
[0118] (Negative electrode) The negative electrode of the lithium secondary battery is the above-mentioned negative electrode for lithium secondary batteries.
[0119] (Separator) The separator of the lithium secondary battery may be, for example, a material having a form such as a porous film, a nonwoven fabric, or a woven fabric, made of a material such as a polyolefin resin, such as polyethylene or polypropylene, a fluororesin, or a nitrogen-containing aromatic polymer. The separator may be formed by using two or more of these materials, or may be formed by laminating these materials. The separator described in JP-A-2000-030686 or US20090111025A1 may also be used.
[0120] (electrolyte) The electrolyte solution in the lithium secondary battery contains an electrolyte and an organic solvent.
[0121] The electrolytes contained in the electrolyte are LiClO4, LiPF6, LiAsF6, LiSbF6, LiBF4, LiCF3SO3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(COCF3), Li(C4F9SO3), LiC(SO2CF3)3, Li2B 10 Cl 10 Examples of the electrolyte include lithium salts such as LiBOB (here, BOB is bis(oxalato)borate), LiFSI (here, FSI is bis(fluorosulfonyl)imide), lithium salts of lower aliphatic carboxylates, and LiAlCl4, and mixtures of two or more of these may be used. Among these, it is preferable to use an electrolyte containing at least one selected from the group consisting of fluorine-containing LiPF6, LiAsF6, LiSbF6, LiBF4, LiCF3SO3, LiN(SO2CF3)2, and LiC(SO2CF3)3.
[0122] Examples of the organic solvent contained in the electrolytic solution include carbonates such as propylene carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, 4-trifluoromethyl-1,3-dioxolan-2-one, and 1,2-di(methoxycarbonyloxy)ethane; 1,2-dimethoxyethane, 1,3-dimethoxypropane, pentafluoropropyl methyl ether, 2,2,3,3-tetrafluoropropyl difluoromethyl ether, tetrahydrofuran, and 2-methyltetrahydrofuran. esters such as methyl formate, methyl acetate, propyl propionate, and γ-butyrolactone; nitriles such as acetonitrile and butyronitrile; amides such as N,N-dimethylformamide and N,N-dimethylacetamide; carbamates such as 3-methyl-2-oxazolidone; sulfur-containing compounds such as sulfolane, dimethyl sulfoxide, and 1,3-propane sultone, or these organic solvents further having a fluoro group introduced therein (organic solvents in which one or more hydrogen atoms have been replaced with fluorine atoms).
[0123] The electrolyte may contain additives such as tris(trimethylsilyl) phosphate and tris(trimethylsilyl) borate.
[0124] As the organic solvent, it is preferable to use a mixture of two or more of these. Among them, a mixed solvent containing a carbonate is preferable, and a mixed solvent of a cyclic carbonate and an acyclic carbonate and a mixed solvent of a cyclic carbonate and an ether are more preferable.
[0125] In addition, since the safety of the resulting lithium secondary battery is improved, it is preferable to use an electrolyte solution containing a fluorine-containing lithium salt such as LiPF6 and an organic solvent having a fluorine substituent. The electrolyte and organic solvent contained in the electrolyte solution may be the electrolyte and organic solvent described in WO2019 / 098384A1 or US2020 / 0274158A1.
[0126] <All-solid-state lithium secondary battery> Next, an all-solid-state lithium secondary battery having the above-mentioned negative electrode will be described while explaining the configuration of the all-solid-state lithium secondary battery.
[0127] Fig. 6 is a schematic diagram showing an example of the all-solid-state lithium secondary battery of this embodiment. The all-solid-state lithium secondary battery (lithium secondary battery) 1000 shown in Fig. 6 has a laminate 100 having a positive electrode 110, a negative electrode 120, and a solid electrolyte layer 130, and an exterior body 200 that houses the laminate 100. The all-solid-state lithium secondary battery 1000 may have a bipolar structure in which a positive electrode active material and a negative electrode active material are arranged on both sides of a current collector. A specific example of the bipolar structure is the structure described in JP-A-2004-95400. The materials constituting each member will be described later.
[0128] The laminate 100 may have an external terminal 113 connected to the positive electrode current collector 112 and an external terminal 123 connected to the negative electrode current collector 122. In addition, the all-solid-state lithium secondary battery 1000 may have a separator between the positive electrode 110 and the negative electrode 120.
[0129] The all-solid-state lithium secondary battery 1000 further includes an insulator (not shown) that insulates the laminate 100 from the exterior body 200 , and a sealing body (not shown) that seals the opening 200 a of the exterior body 200 .
[0130] A container molded from a highly corrosion-resistant metal material such as aluminum, stainless steel, or nickel-plated steel can be used as the exterior body 200. Also, a container formed into a bag shape from a laminate film having at least one surface treated to be corrosion-resistant can be used as the exterior body 200.
[0131] Examples of the shape of the all-solid-state lithium secondary battery 1000 include a coin type, a button type, a paper type (or a sheet type), a cylindrical type, a square type, and a laminate type (pouch type).
[0132] The all-solid-state lithium secondary battery 1000 is illustrated as having one laminate 100 as an example, but the present embodiment is not limited to this. The all-solid-state lithium secondary battery 1000 may have a configuration in which the laminate 100 is used as a unit cell, and a plurality of unit cells (laminated bodies 100) are sealed inside an exterior body 200.
[0133] Each component will be described in order below.
[0134] (positive electrode) The positive electrode 110 includes a positive electrode active material layer 111 and a positive electrode current collector 112 .
[0135] The positive electrode active material layer 111 contains a positive electrode active material and a solid electrolyte. The positive electrode active material layer 111 may also contain a conductive material and a binder.
[0136] (solid electrolyte) As the solid electrolyte contained in the positive electrode active material layer 111, a solid electrolyte having lithium ion conductivity and used in a known all-solid-state lithium secondary battery can be adopted. Examples of such solid electrolytes include inorganic electrolytes and organic electrolytes. Examples of inorganic electrolytes include oxide-based solid electrolytes, sulfide-based solid electrolytes, and hydride-based solid electrolytes. Examples of organic electrolytes include polymer-based solid electrolytes. Examples of each electrolyte include the compounds described in WO2020 / 208872A1, US2016 / 0233510A1, US2012 / 0251871A1, and US2018 / 0159169A1, and for example, the following compounds can be mentioned.
[0137] (Oxide-based solid electrolyte) Examples of oxide-based solid electrolytes include perovskite-type oxides, NASICON-type oxides, LISICON-type oxides, garnet-type oxides, and the like. Specific examples of each oxide include the compounds described in WO2020 / 208872A1, US2016 / 0233510A1, and US2020 / 0259213A1, and for example, the following compounds can be mentioned.
[0138] Examples of perovskite-type oxides include Li a La 1-a TiO3 (0 < a < 1) and other Li-La-Ti-based oxides, Li b La 1-b TaO3 (0 < b < 1) and other Li-La-Ta-based oxides, and Li c La 1-c NbO3 (0 < c < 1) and other Li-La-Nb-based oxides, etc.
[0139] Examples of NASICON-type oxides include Li 1+d Al d Ti 2-d (PO4)3 (0 ≤ d ≤ 1), etc. NASICON-type oxides refer to Li m M 1 n M 2 o P p O q (where M1 is one or more elements selected from the group consisting of B, Al, Ga, In, C, Si, Ge, Sn, Sb and Se. M 2 is one or more elements selected from the group consisting of Ti, Zr, Ge, In, Ga, Sn and Al. m, n, o, p and q are any positive numbers.
[0140] LISICON-type oxides include Li4M 3 O4-Li3M 4 O4(M 3 is one or more elements selected from the group consisting of Si, Ge, and Ti. 4 is one or more elements selected from the group consisting of P, As and V.
[0141] Garnet-type oxides include Li7La3Zr2O 12 (LLZ) and other Li-La-Zr oxides.
[0142] The oxide-based solid electrolyte may be a crystalline material or an amorphous material.
[0143] (Sulfide solid electrolyte) The sulfide-based solid electrolytes include Li2S-P2S5-based compounds, Li2S-SiS2-based compounds, Li2S-GeS2-based compounds, Li2S-B2S3-based compounds, LiI-Si2S-P2S5-based compounds, LiI-Li2S-P2O5-based compounds, LiI-Li3PO4-P2S5-based compounds, and Li 10 GeP2S 12 Compounds based on the above-mentioned compounds can be mentioned.
[0144] In this specification, the expression "sulfide-based compound" referring to a sulfide-based solid electrolyte is used as a general term for solid electrolytes mainly containing raw materials such as "Li2S" and "P2S5" described before "sulfide-based compound". For example, Li2S-P2S5-based compounds include solid electrolytes mainly containing Li2S and P2S5 and further containing other raw materials. The ratio of Li2S contained in the Li2S-P2S5-based compound is, for example, 50 to 90 mass% with respect to the entire Li2S-P2S5-based compound. The ratio of P2S5 contained in the Li2S-P2S5-based compound is, for example, 10 to 50 mass% with respect to the entire Li2S-P2S5-based compound. In addition, the ratio of other raw materials contained in the Li2S-P2S5-based compound is, for example, 0 to 30 mass% with respect to the entire Li2S-P2S5-based compound. In addition, the Li2S-P2S5-based compound also includes solid electrolytes with different mixing ratios of Li2S and P2S5.
[0145] Li2S-P2S5 based compounds include Li2S-P2S5, Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, Li2S-P2S5-LiI-LiBr, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, and Li2S-P2S5-Z. m S n (m and n are positive numbers. Z is Ge, Zn or Ga.)
[0146] Li2S-SiS2-based compounds include Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-SiS2-P2S5-LiCl, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li2SO4, and Li2S-SiS2-Li x MO y (x and y are positive numbers. M is P, Si, Ge, B, Al, Ga, or In.)
[0147] Examples of Li2S-GeS2 based compounds include Li2S-GeS2 and Li2S-GeS2-P2S5.
[0148] The sulfide-based solid electrolyte may be a crystalline material or an amorphous material.
[0149] (Hydride-based solid electrolyte) Examples of hydride-based solid electrolyte materials include LiBH4, LiBH4-3KI, LiBH4-PI2, LiBH4-P2S5, LiBH4-LiNH2, 3LiBH4-LiI, LiNH2, Li2AlH6, Li(NH2)2I, Li2NH, LiGd(BH4)3Cl, Li2(BH4)(NH2), Li3(NH2)I, and Li4(BH4)(NH2)3.
[0150] (Polymer-based solid electrolyte) Examples of the polymer solid electrolyte include organic polymer electrolytes such as polyethylene oxide polymer compounds and polymer compounds containing at least one selected from the group consisting of polyorganosiloxane chains and polyoxyalkylene chains. Also, so-called gel-type electrolytes in which a non-aqueous electrolyte solution is held in a polymer compound can be used.
[0151] Two or more solid electrolytes can be used in combination as long as the effects of the invention are not impaired.
[0152] (Conductive materials and binders) The conductive material of the positive electrode active material layer 111 may be the material described in the above (Conductive material). The proportion of the conductive material in the positive electrode mixture may be the same as that described in the above (Conductive material). The binder of the positive electrode may be the material described in the above (Binder).
[0153] (Positive electrode current collector) For the positive electrode current collector 112 of the positive electrode 110, the materials explained above in (positive electrode current collector) can be used.
[0154] An example of a method for supporting the positive electrode active material layer 111 on the positive electrode current collector 112 is a method for pressure molding the positive electrode active material layer 111 on the positive electrode current collector 112. Cold pressing or hot pressing can be used for pressure molding.
[0155] Alternatively, a mixture of the positive electrode active material, the solid electrolyte, the conductive material, and the binder may be made into a paste using an organic solvent to prepare a positive electrode mixture, and the obtained positive electrode mixture may be applied onto at least one surface of the positive electrode current collector 112, dried, and pressed to adhere, thereby causing the positive electrode active material layer 111 to be supported on the positive electrode current collector 112.
[0156] Alternatively, a mixture of the positive electrode active material, the solid electrolyte, and the conductive material may be made into a paste using an organic solvent to prepare a positive electrode mixture, and the obtained positive electrode mixture may be applied onto at least one surface of the positive electrode current collector 112, dried, and sintered to cause the positive electrode active material layer 111 to be supported on the positive electrode current collector 112.
[0157] As the positive electrode active material that can be used in the positive electrode mixture, the same positive electrode active material as explained above in (Positive electrode active material) can be used.
[0158] As the organic solvent that can be used for the positive electrode mixture, the same organic solvent that can be used when making the positive electrode mixture into a paste as described above in (positive electrode current collector) can be used.
[0159] The method for applying the positive electrode mixture to the positive electrode current collector 112 includes the methods described above in (Positive electrode current collector).
[0160] The positive electrode 110 can be manufactured by the method described above. Specific combinations of materials used for the positive electrode 110 include the combinations shown in Table 1 with the positive electrode active material.
[0161] [Table 1]
[0162] [Table 2]
[0163] [Table 3]
[0164] (Negative electrode) The negative electrode 120 has a negative electrode active material layer 121 and a negative electrode current collector 122. The negative electrode active material layer 121 contains the negative electrode active material of this embodiment.
[0165] (solid electrolyte layer) The solid electrolyte layer 130 includes the solid electrolyte described above.
[0166] An example of a method for producing the solid electrolyte layer 130 is to apply an inorganic solid electrolyte to the surface of the positive electrode active material layer 111 of the above-mentioned positive electrode 110 by sputtering, or to apply a paste-like mixture containing a solid electrolyte, and then dry it. In the latter case, the solid electrolyte layer 130 may be formed by pressing the dried product and further pressing the product by cold isostatic pressing (CIP).
[0167] The laminate 100 can be produced by laminating the negative electrode 120 on the solid electrolyte layer 130 provided on the positive electrode 110 as described above, using a known method, in such a manner that the negative electrode active material layer 121 is in contact with the surface of the solid electrolyte layer 130.
[0168] According to the lithium secondary battery having the above-mentioned configuration, since the negative electrode active material containing the above-mentioned PC material is used in the negative electrode, the lithium battery has a high capacity and excellent cycle characteristics.
[0169] As one aspect, the present invention also includes the following embodiment.
[0170] <1> A phosphorus-carbon composite material containing phosphorus atoms and carbon atoms, The phosphorus atom content in the phosphorus-carbon composite material is 10% by mass or more and 95% by mass or less, the content of carbon atoms in the phosphorus-carbon composite material is 5% by mass or more and 90% by mass or less; A phosphorus-carbon composite material having a peak in the XPS spectrum indicating bonding between phosphorus atoms and carbon atoms.
[0171] <2> A phosphorus-carbon composite material containing phosphorus atoms and carbon atoms, The phosphorus atom content in the phosphorus-carbon composite material is 10% by mass or more and 95% by mass or less, the content of carbon atoms in the phosphorus-carbon composite material is 5% by mass or more and 90% by mass or less; In the XRD profile measured using CuKα radiation, the intensity I at 2θ=20° 20 , Intensity I at 2θ=26.3° 26.3 , and the intensity at 2θ=40° I 40 A phosphorus-carbon composite material that satisfies the following formulas (1) to (3). |P| / |B|<2 …(1) P=I 26.3 -I 40 …(2) B=(I 20 -I 40 ) × (26.3-40) / (20-40) … (3)
[0172] <3> A phosphorus-carbon composite material containing phosphorus atoms and carbon atoms, The phosphorus atom content in the phosphorus-carbon composite material is 10% by mass or more and 95% by mass or less, the content of carbon atoms in the phosphorus-carbon composite material is 5% by mass or more and 90% by mass or less; A core particle including a phosphorus atom; and a carbon coating covering the surface of the core particle.
[0173] Although the preferred embodiment of the present invention has been described above with reference to the accompanying drawings, the present invention is not limited to the above embodiment. The shapes and combinations of the components shown in the above embodiment are merely examples, and various modifications can be made based on design requirements, etc., without departing from the spirit of the present invention. EXAMPLES
[0174] The present invention will be described below with reference to examples, but the present invention is not limited to these examples.
[0175] In the present examples, the physical properties were measured by the following methods.
[0176] [Thermogravimetry] A 10 mg sample of the phosphorus-carbon composite material is precisely weighed and used as a sample. Using a thermogravimetric analyzer, the sample is heated from 50°C to 780°C at a heating rate of 10°C / min under a nitrogen stream, and the change in weight is measured.
[0177] [XPS spectrum] The measurement was performed according to the above-mentioned (XPS spectrum measurement conditions).
[0178] [Raman spectrum] The measurement was performed according to the above-mentioned (Raman spectrum measurement conditions).
[0179] [TEM image] The images were taken according to the above-mentioned (TEM photographing conditions).
[0180] [XRD profile] The measurement was performed according to the above-mentioned (XRD profile measurement conditions).
[0181] [Raw materials] In the examples and comparative examples, the following materials were used.
[0182] (Rin) Rasa Industrial Black Phosphorus
[0183] (Carbon materials) CSCNT: GSI Creos MCMB1:MG10, manufactured by China Steel Chemical Co., Ltd. MCMB2:MG11, manufactured by China Steel Chemical Co., Ltd. MCMB3:MG12, manufactured by China Steel Chemical Co., Ltd. Graphite: SNO15, manufactured by SEC Carbon AB: Denka Black HS100, manufactured by Denka Co., Ltd. SWCNT: GSI Creos
[0184] [Examples 1 to 7] Black phosphorus and a carbon material were weighed out in the ratio shown in Table 4 (total amount 0.5 g) and mixed in a ball mill under the following conditions to obtain a PC material. (Ball mill mixing conditions) Equipment:Retsch PM-100 Container: 50mL ZrO2 container Media: ZrO2 5mmφ ball, 60g Atmosphere: Argon gas filled Sample amount: 0.5g of raw material mixture Ball / powder ratio: 120 (by weight) Mixing time: 12 hours
[0185] [Comparative Examples 1 and 2] Black phosphorus and a carbon material were weighed out in the ratio shown in Table 4 (total amount 0.5 g) and mixed in a mortar to obtain a PC mixture.
[0186] [Table 4]
[0187] [evaluation] Using the obtained materials, a battery for evaluation was produced by the following method and evaluated. The evaluation results are shown in Table 5.
[0188] (Preparation of evaluation battery) (1) Preparation of the negative electrode The PC material or PC mixture, conductive material, and binder were weighed and mixed at a ratio of [PC material or PC mixture]:[conductive material]:[binder] = 80:10:10 (mass ratio). The materials used are as follows: Binder: Polyvinylidene fluoride (PVdF) Kureha KF Polymer #1100 (Kureha Corporation) Conductive material: Acetylene black, Denka Black HS100 (manufactured by Denka Co., Ltd.)
[0189] The mixture was kneaded with a solvent (NMP (N-methyl-2-pyrrolidone)) in an agate mortar to prepare a negative electrode slurry. At this time, the slurry concentration was adjusted so that the content of the negative electrode active material (the total of the PC material or PC mixture, the conductive material, and the binder) in the negative electrode slurry was 30 to 60 mass%.
[0190] The negative electrode slurry was applied to a copper foil current collector using a doctor blade, and then the negative electrode was dried with air at 120°C for 1 hour to remove the solvent, obtaining a laminate. The obtained laminate was pressed under 10 mPa for 10 seconds, and then further dried in vacuum at 120°C for 12 hours to obtain a negative electrode.
[0191] The above-mentioned preparation of the negative electrode slurry and the preparation of the negative electrode were carried out in a glove box in an argon atmosphere.
[0192] (2) Fabrication of lithium-ion secondary batteries A lithium-ion secondary battery (coin-type battery R2032) was fabricated by combining the negative electrode, counter electrode, electrolyte, and separator prepared in (1). The battery was assembled in a glove box with an argon atmosphere.
[0193] Metallic lithium foil was used as the counter electrode.
[0194] As the electrolyte, a mixed solution in which 10 mass % of fluoroethylene carbonate (FEC) was added to a LiPF6 solution (Kishida Chemical Co., Ltd.) was used.
[0195] The LiPF6 solution used was a solution in which LiPF6 was dissolved at 1 mol / L in a mixed solvent of ethylene carbonate (EC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC) in a volume ratio of 30:35:35.
[0196] As the separator, a laminated film separator (16 μm thick) was used in which a heat-resistant porous layer was laminated on a polyethylene porous film.
[0197] (Evaluation 1. Discharge capacity) Using the above evaluation battery, a charge / discharge test was carried out under the following conditions at 25°C. Here, the theoretical capacity of phosphorus was 2600mAh / g, and the 1C current at which the electrode capacity was charged or discharged in 1 hour was 2600mA / g. In the charge / discharge test, the 1C current was calculated from the mass of phosphorus contained in the negative electrode. The definition of 1C in the examples is the same below. Minimum charging voltage: 0.005V Charging current: 0.1C (1C=2600mA / g) Maximum discharge voltage: 2.0V Discharge current: 0.1C (1C=2600mA / g)
[0198] In evaluation 1, a battery with a discharge capacity of 500 mAh / g or more was judged to be good, and a battery with a discharge capacity of less than 500 mAh / g was judged to be bad. For reference, the theoretical discharge capacity of graphite, which is a carbon material, is 372 mAh / g.
[0199] (Evaluation 2. Cycle characteristics) The above evaluation battery was used to evaluate cycle characteristics by repeatedly charging and discharging under the following conditions at 25°C. The cycle characteristics were evaluated using the ratio (D100 / D1) of the discharge capacity D100 at the 100th cycle at a 1C rate current to the charge capacity D1 at the 1st cycle. The larger D100 / D1 indicates a higher retention rate of discharge capacity with cycling, and therefore it can be determined that the material is excellent as a negative electrode active material. Minimum charging voltage: 0.005V Charging current: 1C (1C=2600mA / g) Maximum discharge voltage: 2.0V Discharge current: 1C (1C=2600mA / g)
[0200] In evaluation 2, a product with D100 / D1 of 50% or more was judged as good, and a product with D100 / D1 of less than 50% was judged as bad.
[0201] [Table 5]
[0202] 7 is a graph showing the results of thermogravimetry of the PC materials prepared in Examples 1 and 4 to 7, and the PC mixture prepared in Comparative Example 2. As shown in FIG. 7, all of the PC materials had a WL 620 / WL 780 was greater than 0.1 and less than 0.9.
[0203] In addition, the PC material of Example 7 is WL 620 / WL 780 was 0.75, which was larger than those of the PC materials of the other Examples. It is believed that the SWCNT carbon material used in Example 7 has a smaller amount of edge sites relative to the amount of carbon atoms than other carbon materials. It is believed that a carbon material with fewer edge sites produces a smaller amount of PC bonds than a carbon material with more edge sites. It is believed that this difference in the amount of PC bonds is reflected in the difference in the results of thermogravimetry between the PC material of Example 7 and the PC materials of the other Examples.
[0204] In contrast, the PC mixtures of Comparative Examples 1 and 2 had a WL 620 / WL 780 was larger than 0.9, a steep weight loss was observed at measurement temperatures of around 350° C. to 450° C., and almost no weight loss was observed at temperatures of 500° C. or higher. Therefore, the PC mixtures of Comparative Examples 1 and 2 do not form new bonds capable of withstanding high temperatures of 620° C. or higher, and can be said to be in a state of a mixture of the raw materials, phosphorus and carbon material.
[0205] Fig. 8 shows the XPS spectra of the PC materials prepared in Examples 1 to 5 and 7. As shown in Fig. 8, a peak appears in the range of 132 to 136 eV in each of the PC materials, confirming the formation of PC bonds.
[0206] On the other hand, although not shown in FIG. 8, the PC mixtures of Comparative Examples 1 and 2 had no peak in the range of 132 to 136 eV in the XPS spectrum, and no PC bond could be confirmed.
[0207] Fig. 9 shows the XRD profiles of the PC materials prepared in Examples 1 to 7 and the PC mixtures prepared in Comparative Examples 1 and 2. As shown in Fig. 9, in none of the PC materials was a peak confirmed at 2θ = 26.3°, and it can be determined that the carbon material was amorphous or was so fine that the crystalline state could not be confirmed.
[0208] On the other hand, in the PC mixtures of Comparative Examples 1 and 2, a peak was observed at 2θ=26.3°, which indicates that the amorphization of the carbon material was insufficient.
[0209] Fig. 10 is a graph showing the discharge capacity up to 100 cycles of lithium secondary batteries using the PC materials of Examples 1 to 7 and Comparative Example 2. When the battery performance was evaluated, it was found that the PC materials of Examples 1 to 7 had high discharge capacity and excellent cycle characteristics when used as negative electrode active materials. In contrast, the PC mixture of Comparative Example 2 could not obtain a sufficient discharge capacity, and the cycle characteristics were extremely poor compared to the Examples.
[0210] From the above results, it was confirmed that the present invention is useful. [Explanation of symbols]
[0211] 3,120...negative electrode, 10...lithium secondary battery, 50...particle, 51...core particle, 52...carbon film, 1000...all-solid-state lithium secondary battery (lithium secondary battery)
Claims
1. A phosphorus-carbon composite material containing phosphorus atoms and carbon atoms, The phosphorus atom content in the phosphorus-carbon composite material is 10% by mass or more and 95% by mass or less, the content of carbon atoms in the phosphorus-carbon composite material is 5% by mass or more and 90% by mass or less; Weight loss rate WL at a measurement temperature of 620°C obtained by thermogravimetry under the following conditions 620 and the weight loss rate WL at a measurement temperature of 780°C 780 Relative to WL 620 / WL 780 is 0.1 or more and 0.9 or less. (Thermogravimetric measurement) 10 mg of the phosphorus-carbon composite material is precisely weighed as a sample, and a thermogravimetric analyzer is used to measure the change in weight when the sample is heated from 50° C. to 780° C. at a temperature increase rate of 10° C. / min in a nitrogen stream. (Weight reduction rate) The ratio of the weight of the sample at the measurement temperature to the weight of the precisely weighed sample is defined as the weight loss rate (wt %) at the measurement temperature.
2. Weight loss rate WL at a measurement temperature of 300° C. obtained by the above thermogravimetry 300 and the weight loss rate WL at a measurement temperature of 600°C 600 Relative to WL 300 / WL 600 The phosphorus-carbon composite material according to claim 1, wherein is -0.1 or more and 0.1 or less.
3. 3. The phosphorus-carbon composite material according to claim 1, which has a peak in an XPS spectrum indicating a bond between a phosphorus atom and a carbon atom.
4. In the XRD profile measured using CuKα radiation, the intensity I at 2θ=20° 20 , Intensity I at 2θ=26.3° 26.3 , and the intensity I at 2θ=40° 40 The phosphorus-carbon composite material according to any one of claims 1 to 3, wherein the phosphorus-carbon composite material satisfies the following formulas (1) to (3). |P| / |B|<2...(1) P=I 26.3 -I 40 …(2) B=(I 20 -I 40 )×(26.3-40) / (20-40) …(3)
5. A core particle including a phosphorus atom; The phosphorus-carbon composite material according to any one of claims 1 to 4, further comprising a carbon coating covering a surface of the core particle.
6. A method for producing a phosphorus-carbon composite material, comprising a step of compounding a carbon material and phosphorus by a mixing and grinding process involving compression.
7. A method for producing a phosphorus-carbon composite material, comprising a step of mixing a carbon material with phosphorus in a ball mill.
8. The carbon material is amorphous carbon, graphite, porous carbon, mesocarbon microbeads, fullerene, carbon nanotubes, graphene, graphene oxide, carbon nitrite (C 3 N 4 8. The method for producing a phosphorus-carbon composite material according to claim 6, wherein the phosphorus-carbon composite material is at least one selected from the group consisting of carbon nanofibers and laminated carbon nanofibers.
9. The method for producing a phosphorus-carbon composite material according to any one of claims 6 to 8, wherein the phosphorus is black phosphorus.
10. A negative electrode active material comprising the phosphorus-carbon composite material according to any one of claims 1 to 5.
11. A negative electrode for a lithium secondary battery comprising the negative electrode active material according to claim 10.
12. A lithium secondary battery comprising the negative electrode for lithium secondary batteries according to claim 11.
Citation Information
Patent Citations
Negative electrode for lithium secondary battery
JP1999067207A
